Pembinaan Pelafalan Huruf Hijaiyyah Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Anak-Anak Di Desa Mattunreng Tellue - Mirnawati, Mirnawati; Ni'mah, Siar; Umar, Umar; Suriati, Suriati (LP2M Universitas Islam Ahmad Dahlan, 2023)
This activity aims to foster children in pronouncing the correct hijaiyyah letters so that they can improve their ability to read the Qur'an. The training took place in Tanatoae Hamlet, Mattunreng Tellue Village, with a focus on children in the village. The coaching method used is to adjust the method of reading the Koran which is common, namely the iqra method. This was chosen by observing the children in this village using the Iqra method in their learning. The results of this coaching can be seen from the development of reading the Qur'an, especially in the pronunciation of hijaiyyah letters which are still not quite right. This coaching is in order to improve human resources, especially for children in the religious field.